Faktor-Faktor yg mempengaruhi Minat Mahasiswa Bekerja di Lembaga Keuangan dengan Jenjang Karir sebagai Moderasi - Sono, Mohammad Gifari; Agustina, Granit; Tahirs, Jemi Pabisangan; Munizu, Musran; Kumagaya, Johannes. P. (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine the factors that influence students' interest in working in financial institutions with career ladder as a moderation. The research method used is quantitative method. The population in this study were regular students at several universities with a sample of 146 people. The sampling method used was purposive sampling. The data used were primary data using the online questionnaire/google form method. The data obtained were analyzed using the Partial Least Square (PLS) analysis technique through Smart PLS software. The results of this study are that the work environment and job market considerations have a significant effect on students' interest in working in financial institutions. Career ladder is unable to moderate the influence of the work environment on students' interest in working in financial institutions. Career ladder is able to moderate job market considerations on students' interest in working in financial institutions.